Pressekriege. Öffentlichkeit und Diplomatie in den deutsch-britischen Beziehungen (1896-1912) - Geppert, Dominik (Veröffentlichungen des Deutschen Historischen Instituts London/ Publications of the German Historical Institute London, 2007)
Taking German-British "newspaper wars" as an example, this study looks at the interaction between the emerging mass press and foreign policy, traditionally conducted as secret diplomacy, in the 25 years before the First World War. "Press feuds" are construed as focal points that highlighted contemporary discourses and the actions of various individuals and social groups. They represented phases in which media and political communication intensified, and in which enemy images were created or confirmed, self-perceptions modified or consolidated. At the same time they presented an opportunity to examine and re-adjust the relationship between diplomacy and the public sphere. The example of Anglo-German relations is particularly suitable for an analys is of the tension between "public opinion" and diplomacy. For diplomatic friction due to hos tile newspaper articles, critical press commentaries, or caricatures seen as insulting, played a crucial role between Germany and Britain in the years 1896 to 1912. At the same time the asse rtion that there was actually no conflict of interests between the two countries, and that these unfortunate "press feuds" were solely responsible for political discord, became the standard argument of all those seeking to improve relations. The background to all this was the massive extension of the boundaries of the public sphere. The dividing line between legitimate general interest and what should be withheld from this interest, was moved. This applied not only to the relationship between public and private, but also to the pair of opposites "public - secret". There was increasing pressure for sectors that had long-since been regarded as the exclusive domain of political and social elites to be opened up to the general public. Governments felt challenged to maintain responsibility for key areas such as foreign policy in the face of this onslaught of publicity. Technical innovations such as the rotary press, the telegraph, and the telephone, along with the emergence of a mass press that saw itself as politically neutral and was financed by advertisements, as well as increased professional self-confidence on the part of the journalists, brought about a dramatic shift in the system of coordinates of publicity and diplomacy. Thus the commercial mass press and its producers fundamentally changed the conditions under which foreign policy was conducted, and indeed is still conducted today.